Sejarah Perkembangan Kaligrafi Arab di Indonesia dan Penggunaannya - Rika Ananda Yunisa; Hanna Nazwa; Lili Sardiani Daulay (Jurnal Shaf, 2024)
As one of the beautiful works of art in Islamic culture, calligraphy also flourished in Indonesia. In addition to being a visual art form, calligraphy also embodies Islamic aesthetic and spiritual principles. The use of calligraphy in mosque decorations, Qur'an mushaf, and other religious objects adds to the majesty and beauty of the sacred writings. Furthermore, calligraphy is a significant component in Indonesian education. Lots of art schools and cultural centres offer calligraphy courses, giving the younger generation the opportunity to understand and inherit this art. The learning of calligraphy covers not just the functional elements, but also the cultural and spiritual values in each stroke of the letter. This research aims to explore the development, use, and impact of Arabic calligraphy in Indonesia, particularly in education. Qualitative research using a library research strategy is the methodology employed, through searching journal articles on the history of Arabic calligraphy in Indonesia.